Perancangan Interior Tempat Edukasi Gelandangan dan Pengemis di Surabaya - Yoel Sugiarto Pratama (Intra, 2017)
The problem of homeless and beggars in urban cities are an uneven social welfare problem between village’s growth and urban growth resulting in social gap that leads to urbanization. The displacement of villagers to the city is not followed by adequate human resource that is resulting, in increasing of urban poverty.                The education place is designed as temporary shelter as well as providing training for a certain period of time and can be their provision for viable livelihood. The concept used is "Local Culture Puzzle" using the local cultural approach and expected to completed a puzzle after finished education in this place. This concept is applied through the design variations.